Contiguity of Islam and Local Tradition on the Hinterland Malays of West Kalimantan - Ibrahim Ibrahim (Ulumuna, 2018)
Islam does not totally reject values and eculture that preceeded over it or previously existed in a given society when it came later to that society. In contrast, Islam gives high respect to local tradition. The presence of Islam actually improves the living order and and good of local culture by means of accomodation, as this is promoted by “Islam Nusantara”. The contiguity of Islam and local traditions can be seen in various ways across Indonesia. This article examines such encounter of Islam and local tradition in the Hinterland Malay of West Kalimantan. This study explores and identifes local practices where Islam and local values are blended. This study shows that the tradition of Pantang Larang, Perladangan (buma), Berobat Kampung, and Tepung Tawar reflect unique relationship between Islam and local tradition where these two elements are mutually integrated. Islam does not change such traditions but reshape them. The Islamic propagation (dakwah) is not carried out by erasing local tradition but by integrating itself into the traditions, making a strong structure of mutually-enforcing religion and tradition.